Knowledge of Basic Health Units’ healthcare professionals regarding the management of syphilis in Lages, Santa Catarina, Brazil (Brazilian Journal of Health Research, 2021)
Introduction: Syphilis is caused by the bacterium Treponema Pallidum. It is a systemic sexually transmitted infection (STI), representing a serious public health problem. During pregnancy, this infection can bring numerous complications to the pregnant woman, such as abortion, intrauterine death, in addition to representing one of the causes of neonatal mortality and morbidity. Objective: To analyze the knowledge of professionals in Basic Health Units (BHU) about the management of syphilis during pregnancy, in Lages, Santa Catarina. Methods: Descriptive and cross-sectional study, with a quantitative approach carried out through a self-administered questionnaire. Forty health professionals participated in the research, including doctors, nurses, nursing technicians and community health agents (CHA). A statistical analysis of non-parametric data was performed using the Kruskal-Wallis test, considering p
Keywords: Syphilis Congenital; Pregnancy Complications; Infectious; Health Professional